Effects of experimental design and its role in interpretation of results - Shelton, N.W.; Tokach, Michael D.; DeRouchey, Joel M.; Murray, Leigh W.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 256 weanling pigs (PIC TR4 × 1050, initially 13.8 lb and 21 d of age) were used in a 28-d growth trial to compare allotment methods of a completely randomized design (CRD) and a randomized complete block design (RCBD). Two treatments were used to compare these designs: a negative control with no antibiotic or growth promoter and a positive control with 35 g/ton of Denagard (Novartis Animal Health), 400 g/ton of chlortetracycline, and zinc from zinc oxide at 3,000 and 2,000 ppm in Phases 1 and 2, respectively. Experimental diets were fed in 2 phases: Phase 1 from d 0 to 14 and Phase 2 from d 14 to 28. Eight replications of each dietary treatment were used for each experimental design. The first statistical model examined dietary treatment, experimental design, and the design × dietary treatment as fixed factors. With the exception of pens in the CRD having a trend for improved (P < 0.07) F/G from d 0 to 14 compared with pens in the RCBD, no other design or design × dietary treatment differences were detected (P > 0.11) for any responses variables, indicating that treatment means reacted similarly in each of the experimental designs. In both the CRD and the RCBD, pig weights were increased (P < 0.003) with supplementation of growth promoters on d 14 and 28. Variation of weight within pen remained the same in the CRD from d 0 to 28 at approximately 20% but increased from 3% on d 0 to 10% on d 28 for the RCBD. Dietary addition of growth promoters increased (P < 0.003) ADG and ADFI and improved F/G (P < 0.04) in both the CRD and RCBD from d 0 to 14, with lower P-values for the CRD than the RCBD. From d 14 to 28, the CRD detected an increase (P < 0.001) in ADG and ADFI with dietary addition of growth promoters, and the RCBD detected an increase (P < 0.001) only in ADFI. Over the entire 28-d trial, growth promoters increased (P < 0.001) ADG and ADFI and improved (P < 0.03) F/G in the CRD and increased (P < 0.02) ADG and ADFI in the RCBD. Lower standard errors for the difference were also estimated for ADG and F/G in the CRD than in the RCBD from d 0 to 28. The average corrected relative efficiency for each of the three periods was 2.08 for ADG, 5.05 for ADFI, and 0.80 for F/G. The gain and intake values suggest that the added variation explained by blocks in the RCBD was beneficial for achieving a more reduced estimate of σ2error compared with analyzing that particular data set as a CRD. The variance ratios of the CRD to RCBD from d 0 to 28 depict the different responses well with ADG at 0.67, ADFI at 1.70, and F/G at 0.22. When these ratios were compared with an F-test, they were well below the upper critical limit of 4.60, suggesting that the CRD offered estimates for σ2error similar to those of the RCBD. With the same estimate for σ2error, the non-centrality parameter for each design would be similar, and therefore, the increase in degrees of freedom (DF) for the error term would lead to greater power to detect differences in the CRD. Additional studies are needed to verify these results and determine whether blocking is an efficient use of error DF.
Keywords: Allotment; Experimental design; Data interpretation; Swine